Effect of excess superthermal hot electrons on finite amplitude ion-acoustic solitons and supersolitons in a magnetized auroral plasma - Rufai, O.R.; Bharuthram, R.; Singh, S.V.; Lakhina, G.S. (My University, 2015)
The effect of excess superthermal electrons is investigated on finite amplitude nonlinear ionacoustic waves in a magnetized auroral plasma. The plasma model consists of a cold ion fluid, Boltzmann distribution of cool electrons, and kappa distributed hot electron species. The model predicts the evolution of negative potential solitons and supersolitons at subsonic Mach numbers region, whereas, in the case of Cairn’s nonthermal distribution model for the hot electron species studied earlier, they can exist both in the subsonic and supersonic Mach number regimes. For the dayside auroral parameters, the model generates the super-acoustic electric field amplitude, speed, width, and pulse duration of about 18 mV/m, 25.4 km/s, 663 m, and 26 ms, respectively, which is in the range of the Viking spacecraft measurements.
Keywords: Auroral plasma; Ion acoustic solitons; Super solitons; Boltzman distribution; Kappa distribution; Solitons